Functional analysis of human cytomegalovirus UL/b′ region using SCID‐hu mouse model. Issue 8 (4th February 2016) - Dulal, Kalpana; Cheng, Tong; Yang, Lianwei; Wang, Wei; Huang, Ying; Silver, Benjamin; Selariu, Anca; Xie, Cynthia; Wang, Dai; Espeseth, Amy; Lin, Yanzhen; Wen, Lanling; et al.
Abstract : Human cytomegalovirus (HCMV) attenuated strains, Towne, and AD169, differ from prototypic pathogenic strains, such as Toledo, in that they are missing a ∼15‐kb segment in the UL/b′ region. In contrast to the attenuated strains, Toledo can replicate in human tissue implants in SCID (SCID‐hu) mice. Thus, this model provides a unique in vivo system to study the mechanism of viral pathogenesis. Twenty‐two ORFs have been annotated in the UL/b′ region, including tissue‐tropic genes encoded in a pentameric gH/gl complex. To differentiate the role of the pentameric gH/gl complex versus the functions of other ORFs in the 15‐kb region in supporting viral growth in vivo, a series of recombinant viral strains were constructed and their ability to replicate in SCID‐hu mice was tested. The mutations in the Towne and AD169 strains were repaired to restore their pentameric gH/gl complex and it was found that these changes did not rescue their inability to replicate in the SCID‐hu mice. Subsequently four deletion viruses (D1, D2, D3, and D4) in the 15‐kb region from the Toledo strain were created. It was demonstrated that D2 and D3 were able to grow in SCID‐hu mice, while D1 and D4 were not viable. Interestingly, co‐infection of the implant with the D1 and D4 viruses could compensate their respective growth defect in vivo. The results demonstrated that rescuing viral epithelial tropism is not sufficient to revert the attenuation phenotype of AD169 or Towne, and pathogenic genes are located in the segments missing in D1 and D4 viruses. J. Med. Virol. 88:1417–1426, 2016 . © 2016 Wiley Periodicals, Inc.